Burnout and Its Relationship With Depressive Symptoms in Medical Staff During the COVID-19 Epidemic in China - Huo, Lijuan; Zhou, Yongjie; Li, Shen; Ning, Yuping; Zeng, Lingyun; Liu, Zhengkui; Qian, Wei; Yang, Jiezhi; Zhou, Xin; Liu, Tiebang; Zhang, Xiang Yang (Frontiers in Psychology, 2021)
Objective: The large-scale epidemic of Coronavirus Disease 2019 (COVID-19) has triggered unprecedentedly physical and psychological stress for health professionals. The present study aimed to investigate the prevalence and risk factors of burnout syndrome, and the relationship between burnout and depressive symptoms among the frontline medical staff during the COVID-19 epidemic in China. Methods: A total of 606 frontline medical staff were recruited from 133 cities in China using a cross-sectional survey. The Maslach Burnout Inventory (MBI) was used to assess the level of burnout. Depressive symptoms were assessed by the Patient Health Questionnaire Depression (PHQ-9). Results: During the COVID-19 pandemic, 36.5% of the medical staff experienced burnout. Personal and work-related factors were independently associated with burnout, including age (OR = 0.68, 95% CI: 0.52-0.89, p = .004), family income (OR = 0.72, 95% CI: 0.53-0.99, p = .045), having physical diseases (OR = 2.16, 95% CI: 1.42-3.28, p < .001), daily working hours (OR = 1.35, 95% CI: 1.03-1.77, p = .033), and profession of nurse (OR = 2.14, 95% CI: 1.12-4.10, p = .022). The correlation coefficients between scores of each burnout subscale and scores of depressive symptoms were 0.57 for emotional exhaustion, 0.37 for cynicism, and -0.41 for professional efficacy (all p < .001). Conclusions: Our findings suggested that the prevalence rate of burnout is extremely high in medical staff during COVID-19 pandemic, which is associated with other psychological disturbance, such as depression. Psychological intervention for medical staff is urgently needed. Young, less experienced medical staff, especially the nurses should receive more attention when psychological assistance is provided.